2022
DOI: 10.21101/cejph.a6808
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Borrelia IgG antibodies among individuals from Eastern Slovakia

Abstract: Objectives: Lyme borreliosis is a tick-borne disease of increasing incidence and public concern. Our cross-sectional study was aimed at evaluating seroprevalence of Borrelia burgdorferi in a group of respondents from Eastern Slovakia.Methods: In total, 515 blood samples collected in 2013-2016 were analysed with NovaLisaTM, NovaTec -Borrelia IgG/IgM kit (Immunodiagnostica, Dietzenbach, Germany). Positive and equivocal IgG-antibody results were further examined with immunoblotting (LYMECHECK® OPTIMA IgG and IgM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A study where blood samples from tick-bitten individuals were collected from [2008][2009] showed that 43% of the Aland population had detectable Borrelia C6 IgG/IgM antibodies, which is higher than in Sweden; 35%. Furthermore, Borrelia IgG antibodies were detected in 23% of the Aland population, compared to 17% in Sweden and 4.2-13% in some other European countries [1,[5][6][7][8][9][10]. The seroprevalence of TBE-virus (TBEV) IgG antibodies is 0.4-5.3% in nearby geographical areas such as Norway and Sweden where TBE vaccination is still uncommon for the general population [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A study where blood samples from tick-bitten individuals were collected from [2008][2009] showed that 43% of the Aland population had detectable Borrelia C6 IgG/IgM antibodies, which is higher than in Sweden; 35%. Furthermore, Borrelia IgG antibodies were detected in 23% of the Aland population, compared to 17% in Sweden and 4.2-13% in some other European countries [1,[5][6][7][8][9][10]. The seroprevalence of TBE-virus (TBEV) IgG antibodies is 0.4-5.3% in nearby geographical areas such as Norway and Sweden where TBE vaccination is still uncommon for the general population [11,12].…”
Section: Introductionmentioning
confidence: 99%